Bacterial cellulose-based scaffold: synthesis and surface modification for sustained rifampicin release for topic skin infections treatment - Yamada, Caroline; Lazarini, Silmara C.; do Amaral, Nayara C.; Barud, Hernane S.; Mariano-Neto, Rafael; Gonçalves, Adriano Marques; de Oliveira, Guedmiller Souza; Lustri, Bruna Cardinali [UNESP]; Lustri, Wilton R. (Springer Nature, 2024)
The present work aims to produce bacterial cellulose (BC) using Komagataeibacter hansenii, which was isolated after selective conditions in cultivation at 35 C, which were subjected to surface modifications through methanol treatment to produce membranes with different physical characteristics, which allow its use as device for sustained release of the antibacterial drug rifampicin (RIF) with broad spectrum and bactericidal activity against Gram-positive and Gram-negative species, being able to penetrate bacterial biofilms, for potential use as a dressing for the prevention or treatment of skin and soft-tissue infection (SSTI). Here, BC produced was treated with methanol (BC-MeOH) to obtain optimized membranes for use as sustained-release devices for the antibacterial RIF. Parameters such as fiber densities, thickness, and entanglement were assessed for BC-MeOH impregnated with RIF in methanolic solution (BC-MeOH-RIF) compared to BC in distilled water impregnated with RIF in an aqueous solution (BC-H2O-RIF) concerning the capacity for sustained release of RIF. BC-MeOH-RIF and BC-H2O-RIF were characterized by field emission scanning electron microscopy (FEG-SEM), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR). The comparison between the sustained release capacity of RIF by BC-RIF-MeOH and BC-RIF-H2O by applying the disc diffusion and Franz cell kinetics techniques demonstrated the ability of BC-RIF-MeOH to release, in a sustained manner, for 696 h uninterruptedly. Cell viability analysis showed that MeOH treatment did not interfere the development and adhesion of J774 cells, demonstrating the absence of cytotoxicity after heat treatment. Intermolecular interactions between RIF and BC were accounted for in water and methanol solutions using molecular dynamics simulations (MDS). Both FEG-SEM and MDS demonstrated that the interaction energy of the BC-RIF-MeOH set related to the RIF-BC is stronger in methanol solution than in water. These findings demonstrate that BC-RIF-MeOH can contribute to increase the therapeutic arsenal for bacterial infection treatment of SSTIs.
Keywords: Bacterial cellulose; Sustained drug release; Wound infection